Bone marrow vasculature advanced in vitro models for cancer and cardiovascular research - Campanile, Marzia; Bettinelli, Leonardo; Cerutti, Camilla; Spinetti, Gaia (Frontiers in Cardiovascular Medicine, 2023)
Cardiometabolic diseases and cancer are among the most common diseases worldwide and are a serious concern to the healthcare system. These conditions, apparently distant, share common molecular and cellular determinants, that can represent targets for preventive and therapeutic approaches. The bone marrow plays an important role in this context as it is the main source of cells involved in cardiovascular regeneration, and one of the main sites of liquid and solid tumor metastasis, both characterized by the cellular trafficking across the bone marrow vasculature. The bone marrow vasculature has been widely studied in animal models, however, it is clear the need for human-specific in vitro models, that resemble the bone vasculature lined by endothelial cells to study the molecular mechanisms governing cell trafficking. In this review, we summarized the current knowledge on in vitro models of bone marrow vasculature developed for cardiovascular and cancer research.